L’immaginazione tra memoria, volontà e inventio in Agostino - Salvestrini, Amalia (Aesthetica Preprint, 2023)
The article aims to deepen the aesthetic concept of imagination in the pre-modern age and in particular in Augustine of Hippos’ thought. One develops the topic in three parts. The first part points out the emergence of the notion of imagination starting from the relationship between memory and will as it is treated in the De trinitate concerning the trinity of remembrance. The second part studies the rhetorical constitution of the imagination in its relationship with the rhetorical structuring of the Augustinian concept of memory, also referred to as the notion of invention. The last part exemplifies the conferment of a rhetorical sense of imagination through the productive activity of the craftsman. Therefore, the rhetorical constitution exhibits a concept of imagination understood both as a dynamic force capable of connecting the sensible and the intelligible, and as a free variation of images and memorative notions. By choosing a moment prior to the modern birth of the discipline of aesthetics, the constitution of the idea of imagination from the rhetorical side of its description is thus highlighted.